Motivation for Rehabilitation in Patients With Subacute Stroke: A Qualitative Study - Yoshida, Taiki; Otaka, Yohei; Osu, Rieko; Kumagai, Masashi; Kitamura, Shin; Yaeda, Jun (Frontiers in Rehabilitation Sciences, 2021)
Purpose: Motivation is essential for patients with subacute stroke undergoing intensive rehabilitation. Although it is known that motivation induces behavioral changes toward rehabilitation, detailed description has been lacking. Motivation can be intrinsic or extrinsic; however, it is unclear whether these patients have intrinsic motivation for their daily rehabilitation. In this study, we first examined the factors influencing patients’ motivation through interviews to test if intrinsic motivation exists or not. We then examined the behavioral changes induced by motivation, especially age-related differences. Method: Twenty participants (mean age 65.8 years [standard deviation 13.7]) who had a subacute stroke and underwent rehabilitation at a convalescent hospital were recruited using convenience sampling. Semi-structured interviews were conducted by an occupational therapist with an interview topic guide regarding factors influencing motivation and how it affects behavioral change. Interviews were recorded, transcribed to text, and analyzed by three occupational therapists using thematic analysis. The participants were divided into two groups: aged patients (aged ≥ 65 years) and middle aged patients (aged < 65 years), and data were analyzed according to the groups. This study was conducted according to the consolidated criteria for reporting qualitative studies. Results: Seven core categories were identified as factors influencing patients’ motivation: patients’ goals, experiences of success and failure, physical condition and cognitive function, resilience, influence of rehabilitation professionals, relationships between patients, and patients’ supporters. The first four and last three core categories were further classified as personal and social-relationship factors, respectively. The categories related to intrinsic motivation were not derived. In both age groups, motivation affected the frequency of self-training and activity in daily lives. In some aged patients, however, high motivation restrained their self-training to conserve their physical strength for rehabilitation by professionals. Some aged patients do not express their high motivation through their facial expressions and conversations compared to middle aged patients; therefore, motivation is not always observable in aged patients. Conclusions: Interventions tailored to extrinsic factors are important for maintaining patients’ motivation. Observational evaluation may lead to mislabeling of their motivation, especially for aged patients. Rehabilitation professionals should use validated evaluation scales or patients’ narratives to assess patients’ motivation.